Learning From a Tale of Two Droughts: 2002 vs. 2012. Issue 3 (1st March 2015) - Rodriguez, Alfredo
Abstract : Colorado's most recent droughts occurred in 2002 and 2012. The two events shared many similarities. However, because of lessons learned in 2002, Aurora Water's response to the second drought was different because of a significant investment in personnel, infrastructure, and conservation resources.